Synergy of Glutamatergic and Cholinergic Modulation Induces Plateau Potentials in Hippocampal OLM Interneurons - Hagger-Vaughan, Nicholas; Storm, Johan F. (Frontiers in Cellular Neuroscience, 2019)
Oriens-lacunosum moleculare (OLM) cells are hippocampal inhibitory interneurons that are implicated in regulation of information flow in the CA1 circuit. OLM cells express metabotropic cholinergic (mAChR) and glutamatergic (mGluR) receptors, so modulation of these cells via these receptors may contribute to switching between functional modes of the hippocampus. Using a transgenic mouse line to identify OLM cells, we found that both mAChR and mGluR activation caused the cells to exhibit long-lasting depolarizing plateau potentials following evoked spike trains, and there was also a pronounced synergy between the cholinergic and glutamatergic modulation of the plateau potentials. Both mAChR- and mGluR-induced plateau potentials were eliminated by blocking transient receptor potential (TRP) channels, and pharmacological tests indicated that Group I mGluRs are responsible for the glutamatergic induction of plateaus.